Gallbladder agenesis leading to an unnecessary surgery: a case report - Yin, Zizhen; Liu, Yu (Frontiers in Medicine, 2025)
BackgroundGallbladder agenesis is a rare congenital anomaly of the biliary system. Preoperative diagnosis of gallbladder agenesis is challenging and such conditions are often identified intraoperatively. In this report, we present a case of gallbladder agenesis encountered during laparoscopic cholecystectomy.Case presentationA 47-year-old female patient attended our hospital in August 2023 due to distension and discomfort in the right upper quadrant. Ultrasound images revealed that the patient’s gallbladder was filled with gallstones. The patient was admitted to our hospital for laparoscopic cholecystectomy; however, no gallbladder was visualized during the laparoscopy, and the final diagnosis was congenital absence of the gallbladder.ConclusionThe diagnosis of Gallbladder agenesis remains a challenge, It may lead to an unnecessary surgery if physicians do not pay attention to careful differential diagnosis.